Avaliação tóxica, citotóxica e mutagênica de extratos aquosos de Ipomoea asarifolia (Convolvulaceae) - Silva Filho, Eliezer Fernandes da (2015)
How do Genus Species Ipomoea station included between as weeds commonly found in cultivated areas, especially Ipomoea asarifolia (salsa) reported as a toxic plant species and causes que neurological disorders. There is little studies on the toxicity quantity make consumer cellular and genetic level these plants nos production animals semi-arid region. It was assessed a toxic capacity, cytotoxic and mutagenic of the aqueous extract of species leaves I. asarifolia (Convolvulaceae) about growth roots in Allium cepa bulbs; and about the frequency of micronucleated erythrocytes in bone marrow cells in vivo rodent (micronucleus test). Also it enrolled a median lethal dose (LD50) and studied the effect of weight in males and females and analyzed the behavior of animals (Hippocratic screening). Aqueous extracts of dried leaves (EFS) and Fresh (EFF) of I. asarifolia not presented toxic effects or cytotoxic in Allium cepa bulbs roots strain. Were observed allelopathic effects nos growth of roots. Aqueous extracts of dried leaves showed sublethal effects 5mg/L concentration and 300 mg/L. And the fresh leaves showed stimulatory effects all as concentrations studied. The aqueous extract of dried leaves and fresh not caused toxic effects and cytotoxic. There is not cytotoxic effect or in mutagenic rodent cells. The LD50 was found 754.26 mg/kg. From: No influence of gender (male and female) on the toxic effect, but at concentrations of 300 mg/kg and 600 mg/kg of weight was lost. The results against knowledge producers qua not like dry leaves not harm the production of animals